Novas perspectivas sucessórias: a herança digital - Cesa, Jordana (2024)
Digital heritage is a topic that challenges current legislation in the country due to the speed and innovation of the digital era. In this sense, the present study aims to analyze the debates that arise from the need to regulate issues arising from technological evolution, deeply impacting society and bringing new dilemmas, such as the right to privacy vs. the right to inheritance. In some countries the issue already has a legal guarantee, Brazilian jurisprudence prioritizes the privacy of the deceased, but still faces difficulties in reconciling the rights involved. The draft Brazilian Civil Code of 2024 proposes to include digital assets in the estate, seeking greater legal certainty. With specific regulations, it will be easier to protect the deceased's digital assets and guarantee a fair and balanced transmission to heirs.